Following in the footsteps of smallpox: can we achieve the global eradication of measles? - Morgan Oliver WC (BMC, 2004)
Abstract Background Although an effective measles vaccine has been available for almost 40 years, in 2000 there were about 30 million measles infections worldwide and 777,000 measles-related deaths. The history of smallpox suggests that achieving measles eradication depends on several factors; the biological characteristics of the organism; vaccine technology; surveillance and laboratory identification; effective delivery of vaccination programmes and international commitment to eradication. Discussion Like smallpox, measles virus has several biological characteristics that favour eradication. Humans are the only reservoir for the virus, which causes a visible illness and infection leading to life-long immunity. As the measles virus has only one genetic serotype which is relatively stable over time, the same basic vaccine can be used world-wide. Vaccination provides protection against measles infection for at least 15 years, although efficacy may be reduced due to host factors such as nutritional status. Measles vaccination may also confer other non-specific health benefits leading to reduced mortality. Accurate laboratory identification of measles cases enables enhanced surveillance to support elimination programmes. The "catch-up, keep-up, follow-up" vaccination programme implemented in the Americas has shown that measles elimination is possible using existing technologies. On 17th October 2003 the "Cape Town Measles Declaration" by the World Health Organisation and the United Nations Childrens Fund called on governments to intensify efforts to reduce measles mortality by supporting universal vaccination coverage and the development of more effective vaccination. Summary Although more difficult than for smallpox, recent experience in the Americas suggests that measles eradication is technically feasible. Growing international support to deliver these programmes means that measles, like smallpox, may very well become a curiosity of history.